Morphological descriptors of indigenous chickens: as a selection guide - Chencha Chebo; Aberra Melesse; Simret Betsha (Journal of Applied Animal Research, 2023)
The visual morphologies in animals are associated positively or negatively with production, adaptation, and behavioral characteristics. For rural farmers with limited records, these features are considered reliable phenotypic markers. Thus, this study was intended to explore the unique morphological features of indigenous chickens as a farmer's selection guide. A total of 1,060 adult chickens from four rural districts were investigated for nine morphological traits. The single-comb type, supposed to be of good fertility, was the most prevalent. Yellow and white shanks were predominant, followed by gray, greenish-yellow, green, and black pigmentations. Crested and silky chickens were more frequent in highland areas, whereas naked-neck chickens were observed in lowlands. Chickens of the lowlands have brighter, more uniform plumage colors and yellow shank, beak, and earlobe colors. On the other hand, the highland and mid-altitude chickens are characterized by dark, colorful combinations of various feather colors: laced plumage, white shank, rose, and deformed rose combs. Moreover, multiple correspondence analyses revealed that morphological features have special associations with districts. Thus, the observed morphological heterogeneity of the indigenous chickens can be used as a good indicator of selective breeding. Therefore, the associations of these characteristics with productivity qualities could be confirmed by quantitative and molecular tools.